2018
DOI: 10.1111/ciso.12177
|View full text |Cite
|
Sign up to set email alerts
|

“We Don’t Belong There”: New Geographies of Homelessness, Addiction, and Social Control in Vancouver’s Inner City

Abstract: Drawing on eight years of ethnographic research in Vancouver’s inner city, we explore how aligned processes of gentrification and poverty management are producing new geographies of homelessness, addiction, and social control for young people who use drugs and inhabit the social, spatial, and economic margins of urban space. In particular, we examine the emergence of government‐subsidized supportive housing for youth in this setting. Tracing the experiences of a small number of individuals across time, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…[62] Increased government funding was tied to adopting policies and public health agendas that led to the loss of organizational ownership and the ability of individuals and organizations to improvise and adapt nimbly to changing contexts. [62,63] Thus, we must carefully consider the trade-offs if increased government funding and support is accompanied with regulations that restrict operational independence of harm reduction programs. [62,64] Finally, the waiver of the in-person requirement for buprenorphine inductions has allowed a dramatic change in the accessibility of buprenorphine treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[62] Increased government funding was tied to adopting policies and public health agendas that led to the loss of organizational ownership and the ability of individuals and organizations to improvise and adapt nimbly to changing contexts. [62,63] Thus, we must carefully consider the trade-offs if increased government funding and support is accompanied with regulations that restrict operational independence of harm reduction programs. [62,64] Finally, the waiver of the in-person requirement for buprenorphine inductions has allowed a dramatic change in the accessibility of buprenorphine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[62,63] Thus, we must carefully consider the trade-offs if increased government funding and support is accompanied with regulations that restrict operational independence of harm reduction programs. [62,64] Finally, the waiver of the in-person requirement for buprenorphine inductions has allowed a dramatic change in the accessibility of buprenorphine treatment. SSPs reported that participants who would not have had access to MOUD before were now interested in and starting to access it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A largely quantitative body of research from settings across North America has highlighted various barriers to accessing care among vulnerable youth, including long wait times, age restrictions, a lack of trained providers and access to pharmacotherapies, and experiences of discrimination on the basis of gender, race and sexuality [ 15 19 ]. For young people experiencing street entrenchment, barriers to services are often compounded for those experiencing the concurrent disorders of substance use and mental health issues [ 20 ], and residential instability and mobility across institutional (e.g., government care homes, correctional facilities) and non-institutional (e.g., ‘flop houses’) settings over time [ 21 , 22 ]. Moreover, among vulnerable youth, negative experiences with various forms of institutionalization and care stretching back to their childhoods can lead them to the conclusion that reducing or eliminating drug use are things best accomplished independently, without professional help [ 23 ].…”
Section: Introductionmentioning
confidence: 99%